Evaluation and screening of peanut (Arachis hypogaea L.) germplasm for nutritional and biochemical enhancement with in-vitro assessment of anti-cancer properties - Sania Kabir; Mahmood ul Hassan; Muhammad Kausar Nawaz Shah; Kashif Sarfraz Abbasi; Ata-ur Rehman; Kenneth Chinkwo; Muhammad Zargham Ali (PLoS ONE, 2025)
Peanut breeding increasingly emphasizes nutritional enhancement and bioactive potential to support functional food development. This study assessed twenty-eight peanut genotypes for compositional diversity and invitro anticancer and attributes.Principal component analysis revealed 47.78% of the total variation among genotypes, primarily influenced by protein,oleic acid and phenolic content. Significant variation was observed in fatty acid and phenolic profiles revealing genotypes with superior nutritional and antioxidant properties. High phenolics and antioxidant rich genotypes were further analyzed using invitro assay (Resazurin-red) suggesting possible anticancer effects. LC/MS profiling identified 11 phenolic compounds such as p-coumaric acid and quercetin, associated with antioxidant and chemopreventive effects. Extract from the most bioactive genotypes effectively reduced colon cancer cell viability, suggesting possible anticancer potential. All the genotypes have maintained aflatoxin levels below safety thresholds, confirming their suitability for food use. Overall the findings highlight the potential of nutritionally enhanced peanut germplasm for developing dual purpose varieties with improved health and dietary benefits. These results provide a valuable foundation for breeding programs targeting functional and chemopreventive peanut cultivars. However, further in vivo validation of phenolic-driven anticancer mechanisms is warranted to advance functional peanut varieties.